TINGKAT RELIGIUSITAS : SISWA SMK KELAS XI - Jesika Nindi Arsita, Jesika Nindi Arsita; Rakhmawati, Dini; Gunawan, Singgih (Educatio, 2024)
This research was carried out at SMK N 7 Semarang on class XI students using a quantitative approach with quantitative descriptive methodology. The population studied was class XI TME using saturated sampling techniques. The research results show that the level of student religiosity can be described as follows: the level of high religiosity is 19%, while the level of religiosity is very high at 81%. Furthermore, in terms of aspects of religiosity, the following results were found: the first aspect, namely belief in the existence of God, reached a percentage of 24%; the second aspect, implementing religious values, reached a percentage of 14%; the third aspect, understanding religious sciences, reached a percentage of 21%; the fourth aspect, appreciation of religion, reached a percentage of 17%; and the fifth aspect, being positive according to religious teachings, reached a percentage of 24%.